Verdict spotting: investigating the effects of juror bias, evidence anchors and verdict system in jurors. Issue 3 (4th May 2022) - Curley, Lee J.; Murray, Jennifer; MacLean, Rory; Munro, James; Lages, Martin; Frumkin, Lara A.; Laybourn, Phyllis; Brown, David
Abstract : The Scottish verdict of not proven represents a second acquittal verdict which is not legally defined. Existing research into the influence of the not proven verdict on jury decision making is modest. The main aim of the current study was therefore to investigate the influence of verdict systems (two vs three) on juror decision making. The effect of pre-trial bias and evidence anchors on juror judgements were also examined. One-hundred and twenty-eight mock jurors listened to two homicide vignettes and were asked to rate their belief of guilt of the accused and to give a verdict in both trials. The results suggest that pre-trial bias was a significant predictor of both verdict choice and belief of guilt, whereas evidence anchors were not a significant predictor of either. Finally, both guilty and not guilty verdicts were given with increased frequency in the two-verdict system when compared to the three-verdict system.